Exploring three approaches to psychotherapy - Greenberg, Leslie S.; McWilliams, Nancy; Wenzel, Amy; American Psychological Association (Washington, DC : American Psychological Association, 2014)
Provides an in-depth analysis of what happens in therapy according to three different orientations: cognitive, emotion-focused, and psychodynamic.
Introduction -- Emotion-focused therapy -- Psychodynamic therapy -- Cognitive therapy.
Includes bibliographical references and index.
Keywords: Psychotherapy -- methods; Cognitive Behavioral Therapy -- methods; Emotions; Psychotherapy, Psychodynamic -- methods